Characterization of the role for cadherin 6 in the regulation of human endometrial receptivity - Wei Zhou; Leilani Santos; Evdokia Dimitriadis (BMC, 2020)
Abstract Background The endometrial luminal epithelium is the first point of attachment of embryos during implantation. Failure of embryos to firmly adhere results in implantation failure and infertility. A receptive endometrial luminal epithelium is achieved through the expression of adhesion molecules in the mid-secretory phase and is a requirement for implantation. Cadherin 6 (CDH6) is an adhesion molecule localizing to the endometrial luminal epithelial cell surface in the mid-secretory/receptive phase and knockdown of CDH6 in the Ishikawa cells (receptive endometrial epithelial cell line) compromises cell integrity. However, there are no studies investigating the role of CDH6 on receptivity and infertility. This study aimed to investigate whether CDH6 is dysregulated in the endometrium of women with infertility during the receptive window and the effect of CDH6 on endometrial adhesion and receptivity. Methods The expression and the localization of CDH6 in the human endometrium were determined by immunohistochemistry. Ishikawa cells were used to investigate the functional consequences of CDH6 knockdown on endometrial adhesive capacity to HTR8/SVneo (trophoblast cell line) spheroids in vitro. CDH6 knockdown was assessed by qPCR and immunoblotting. After CDH6 knockdown, the expression of type II cadherin family members and CDH6 functional partners were assessed by qPCR. Two-tailed unpaired student's t-test or one-way ANOVA as appropriate were used for statistical analysis with a significance threshold of P < 0.05. Results A significant reduction of CDH6 immunolocalization was recorded in the luminal and glandular epithelium of endometrium from women with infertility (P < 0.05) compared to fertile group respective cellular compartments in the mid-secretory phase. Functional analysis using Ishikawa cells demonstrated that knockdown of CDH6 (treated with 50 nM CDH6 siRNA) significantly reduced epithelial adhesive capacity (P < 0.05) to HTR8/SVneo spheroids compared to control and other type II cadherin family members likely failed to compensate for the loss of CDH6. The expression levels of CDH6 functional partners, catenin family members were not changed after CDH6 knockdown in Ishikawa cells. Conclusion Together, our data revealed that CDH6 was dysregulated in the endometrium from women with infertility and altered Ishikawa cell adhesive capacity. Our study supports a role for CDH6 in regulating endometrial adhesion and implantation.